The Effects of Gross Domestic Product, Energy Consumption, Urbanization, and Trade Openness on CO₂ Emissions in Indonesia - Salma Suraida Khusna; Sultan Sultan (The Global Academia Publisher, 2026)
Indonesia experienced a 26% increase in CO₂ emissions between 2000 and 2023, from approximately 595,000 tons CO₂e to 752,279,000 tons CO₂e, in line with average annual economic growth of 4.9% and an increase in GDP per capita from US778 to US4,700. This phenomenon reflects the Environmental Kuznets Curve (EKC) paradox, in which the early stages of growth increase emissions, while prior research on the validity of the EKC in Indonesia has shown inconsistencies. This study aims to examine the effects of economic growth (GDP per capita and its square), energy consumption, urbanization, and trade openness on CO₂ emissions in Indonesia during the 2000–2023 period using an Autoregressive Distributed Lag (ARDL) bounds testing regression model. The data used in this study come from the Indonesian Central Statistics Agency (BPS) and include national time series data from 2000 to 2023. The long-run estimates show that GDP per capita has a positive and significant effect on CO₂ emissions (b = 4.8312, p = 0.0009), while GDP per capita squared has a negative and significant effect (b = -0.2841, p = 0.0021), confirming the EKC pattern; energy consumption (b = 0.0021, p = 0.0028) and urbanization (b = 0.0183, p = 0.0191) also increase emissions, whereas trade openness is negative but not significant (b = -0.0031, p = 0.1203). These results are expected to clarify whether the EKC hypothesis holds in Indonesia and whether the pollution haven hypothesis does as well. This research is expected to be useful in identifying the underlying causes of increased emissions and supporting the achievement of sustainable development in Indonesia.